PREDIKSI FRAGMENTASI BATUAN HASIL PELEDAKAN DENGAN PENDEKATAN MODEL KUZ-RAMPADA RENCANA PELEDAKAN BATUGAMPING DI KAMPUS LAPANGAN PPSDM-GEOMINERBA - Awang Suwandhi; Charles Tambunan (PPSDM Geominerba, 2019)
Fragmentation of blasting results is one of the aspects assessed in the training of the 1st Class Blaster whose the plan of blasting is carried out at the PPSDM-Geominerba field campus. The results of blasting must consider three conditions including a fraction size greater than 80 cm (boulder)maximum of 5%, a powder factor (PF) maximum of 0.30 kg/m³, and evenly fragmentation size distribution. Blasting geometry is designed with a vertical level of 8 m, average holes depth of 9.4 m with a slope of 20°, spaced 3.45 m, and burden 2.67 m. Total weight of explosives (ANFO) of 396,3kg charged in to the 18 blast holes with diameter of 76 mm. Rock fragmentation distribution predicted by Kuz-Ram model exposed a final result of blasting containing boulder of 9,53%, PF of 0,28 kg/m³, and uniformity index of 1,39. The design of blasting geometry is modified by changing the burden to 2.4 m and the other parameters being relatively the same. The results of blasting are predicted to leave a boulder of 5.76%, the uniformity index improves to 1.50, but the PF increases by 0.31 kg/m³. The modification is the optimum design of blast geometry that is feasible to be applied at the beginning of blasting activity on the field campus.